Effects of insulin-like growth factor-1 and fibroblast growth factor-2 on the in vitro maturation of bovine oocytes - S. S. Derkach; V. V. Kovpak; O. S. Kovpak; O. A. Valchuk; Y. V. Zhuk; Y. S. Masalovych (Regulatory Mechanisms in Biosystems, 2025)
As of now, the leading method of reproducing highly productive animals in animal husbandry is production of cattle e m bryos in in vitro conditions, in particular transvaginal ultrasound-guided oocyte aspiration with further in vitro maturation, which is currently more popular than the in vivo embryo production. Despite the broad introduction of the technique, this process is artificial, meaning limited percentage of maturated oocytes, and therefore lower final yield of embryos suitable for transplant a tion. Augmenting the success rate of oocyte cultivation in in vitro conditions would mean a greater effectiveness of reproductive technologies. Therefore, the objective of our study was to improve the culture medium for maturation of bovine oocytes by co m paring the effects of different concentrations of insulin-like growth factor (IGF-1) and the fibroblast growth factor 2 (FGF2). For this purpose, the cumulus cell-oocyte complexes were divided into six experimental groups: control and groups with different concentrations (50 and 100 ng/cm 3 ) of insulin-like and fibroblast growth factors and their combination, comprising 50 ng/cm 3 of each. The effects of the growth factors were assessed by analyzing the morphological maturity of the oocytes (the cumulus e x pansion index and percentage of oocytes at the MII stage) and also the parameters of embryonic development (the percentage of cleavage and yield of blastocysts). The study revealed that insulin-like growth factor, regardless of concentration, provided no statistically significant increase in the percentage of blastocysts formed, compared with the control. Meanwhile, addition of 50 ng/cm 3 of fibroblast growth factor produced a significant, although not always statistically significant, increase in the studied parameters. The greatest support of maturation was achieved in the group with the combination of growth factors, which pr o vided the highest level of blastulation, accounting for 31.7 ± 2.9%, and a significant difference compared with the control. An optimal strategy for increasing the effeciency of maturation of bovine oocytes in in vitro conditions was a combined enrichment of the culture medium with of 50 ng/cm 3 of IGF and 50 ng/cm 3 of FGF 2, leading to the highest yield of mature oocytes that were competent for fertilization and further embryonic development of gametes.